Compatibilization of Isotactic Polypropylene (iPP) and High-Density Polyethylene (HDPE) with iPP–PE Multiblock Copolymers - Xu, Jun; Eagan, James M; Kim, Sung-Soo; Pan, Sanshui; Lee, Bongjoon; Klimovica, Kristine; Jin, Kailong; Lin, Ting-Wei; Howard, Micah J; Ellison, Christopher J; LaPointe, Anne M; Coates, Geoffrey W; et al. (Macromolecules, 2018)
A series of isotactic polypropylene (iPP) and polyethylene (PE) diblock, tetrablock, and hexablock copolymers (BCPs) were synthesized with tunable molecular weights using a hafnium pyridylamine catalyst. The BCPs were melt blended with 70 wt % high-density PE (HDPE) and 30 wt % iPP commercial homopolymers at concentrations between 0.2 and 5 wt %. The resulting blend morphologies were investigated using TEM, revealing uniformly dispersed iPP droplets ranging progressively in size with increasing BCP content from three-quarters to one-quarter of the diameter of the uncompatibilized mixture. Tensile tests revealed a dramatic enhancement in toughness based on the strain at break which increased from 10% for the unmodified blend to more than 300% with just 0.2 wt % BCP and over 500% with the addition of 0.5 wt % BCP or greater. Incorporation of BCPs in blends also improved the impact toughness, doubling the Izod impact strength to a level comparable to the neat HDPE with just 1 wt % additive. These improved blend properties are attributed to enhanced interfacial strength, which was independently probed using T-peel adhesion measurements performed on laminates composed of HDPE/BCP/iPP trilayers. Thin (ca. ≤100 nm thick) BCP films, fabricated by high-temperature spin coating and molded between the homopolymer films, significantly altered the laminate peel strength, depending on the molecular weight and molecular architecture of the block copolymer. Multilayer laminates containing no BCP or low molecular weight diblock copolymer separated by adhesive failure during peel testing. Sufficiently high molecular weight iPP–PE diblock copolymers and iPP–PE–iPP–PE tetrablock copolymers with significantly lower block molecular weights exhibited cohesive failure of the HDPE film rather than adhesive failure. We propose adhesion mechanisms based on molecular entanglements and cocrystallization for tetrablocks and diblocks, respectively, to account for these findings. These results demonstrate exciting opportunities to recycle the world’s top two polymers through simple melt blending, obviating the need to separate these plastics in mixed waste streams.